TINGKAT PENGETAHUAN PENGGUNAAN OBAT ANTIBIOTIK DI TELUKJAMBE TIMUR KARAWANG - Tegar Wiguna; Desi Sintia; Listia Nurkholifah; Naufal Rizal; Silky Maulina; Theshinta Berliana; Warsono Warsono (Berkala Ilmiah Mahasiswa Farmasi Indonesia, 2022)
Introduction : Antibiotics are the most frequently prescribed drugs for patients but there are still many people who do not know about the use of antibiotics, causing inaccuracy in the use of antibiotics and resulting in drug resistance to germs. Methods: The research method used is descriptive method with cross sectional design. The study was carried out in East Jambe Bay in December 2021. The sampling technique in this study was accidental sampling with inclusion criteria of 20-50 years old, people in the East Jambe Bay area. Data retrieval conducted direct interviews with the number of respondents 30 to obtain primary data. Respondents who took part in this study found 30 people who were members of the East Telukjambe community and met the research inclusion factors. Results: The results of the accidental sampling test showed a significant relationship between gender and knowledge of the use of antibiotics. The level of health awareness is not only influenced by attitude factors, but also by several other individuals, from the results of this study it can be seen that respondents have a higher level of knowledge about antibiotics in answering how to use good and sufficient antibiotics. Conclusion: Based on the research results obtained from 30 respondents, the level of knowledge of the people in Telukjambe Timur towards the use of antibiotics is in the less category as many as 10 people (10%), while in the good category as many as 20 people (20%). So it can be said that the category of public knowledge about antibiotics is in sufficient.